Tikhonov Theorem for Differential Equations with Singular Impulses - Akhmet, M.; Çağ, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
The paper considers impulsive systems with singularities. The main novelty of the present research is that impulses (impulsive functions) are singular. This is beside singularity of differential equations. The most general Tikhonov theorem for the impulsive systems s obtained. Illustrative examples with simulations are given to support the theoretical results.